Analysis of relation between hypoxia PET imaging and tissue-based biomarkers during head and neck radiochemotherapy. (1st November 2016) - Bittner, Martin-Immanuel; Wiedenmann, Nicole; Bucher, Sabine; Hentschel, Michael; Mix, Michael; Rücker, Gerta; Weber, Wolfgang A.; Meyer, Philipp T.; Werner, Martin; Grosu, Anca-Ligia; Kayser, Gian
Abstract: Background: Tumor hypoxia is associated with poor prognosis and outcome and can be visualized using 18F-MISO-positron emission tomography (PET) imaging. The goal of this study was to evaluate the correlation between biological markers and biological imaging in a group of patients in whom a correlation between biological imaging and outcome has previously been demonstrated. Material and methods: In a prospective pilot project, 16 patients with locally advanced cancer of the head and neck underwent 18F-MISO-PET scans before and during primary radiochemotherapy in addition to 18F-FDG-PET and computed tomography (CT). Tumor biopsies were stained for three tissue-based markers (Ku80, CAIX, CD44); in addition, human papillomavirus (HPV) status was assessed. H-scores of marker expression were generated and the results were correlated with the biological imaging and clinical outcome. Results: No statistically significant correlation was established between the H-scores for Ku80, CD44 and CAIX or between any of the H-scores and the imaging variables (tumor volume on 18F-FDG-PET in ml, hypoxic subvolume as assessed by 18F-MISO-PET in ml, and SUVmax tumor/SUVmean muscle during the 18F-MISO-PET). A statistically significant negative correlation was found between CD44 H-score and HPV status (p = .004). Cox regression analysis for overall survival and recurrence-free survival showed one significant result for CAIX being associated with improved overall survival [hazard ratio 0.96 (0.93–1.00), p = .047]. Conclusion: Expression of Ku80, CAIX and CD44 as assessed by immunohistochemistry of tumor biopsies were not correlated to one another or the biological imaging data. However, there was a significant influence of CAIX on overall survival and between CD44 and HPV.